New features correction of the dyslipidemia in patients with diabetes mellitus and metabolic cardiovascular risk factors - V. V. Syvolap; M. P. Gerasko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2014)
The prospects of using new drug of statine class – pitavastatine – in the prophylaxis and treatment of cardiovascular diseases have been considered in this review. The data of international іnvestigations on the comparative effi cacy of pitavastatine have been given; its pleiotropic effects, high profi le safety and tolerance, the decrease in the risk of drugs’ interaction have been shown.